Evaluación de la eficiencia del gasto social en los países EU15 con análisis envolvente de datos y métodos cluster borrosos; Evaluation of the efficiency of social spending in EU15 countries with data envelopment analysis and fuzzy clustering methods - Jorge de Andrés Sánchez; Ángel Gabriel Belzunegui Eraso; Francesc Valls Fonayet (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2020)
– In the study of welfare systems, the relation of the social expenditure and the indicators of vulnerability as poverty rates or income inequality indexes focus a great interest in the literature. In this way, we evaluate the productivity of social transfer policies of EU15 states, which are the countries with more consolidated Welfare States within EU28, during the period 2011-2015, with data envelopment analysis. Subsequently, with a fuzzy clustering method we identify the existing patterns of social expenditures and their efficiency. We identify three groups. The first of them embeds most of the Nordic and continental welfare states. The second group is only made up with Luxembourg and Ireland, that are the countries with the lowest social spending but at the same time, they are within the group of efficient countries. The third group is made up of Mediterranean welfare states and United Kingdom and they are the less efficient countries in reducing vulnerability indexes.
Keywords: C49; F02; H50; H53; 330; income inequality; poverty risk; efficient frontiers; data envelopmentanalysis; fuzzy clustering